Anthropological interference on the vegetation of Wassaniya Forest Reserve of Sokoto State Nigeria - Muhammad, Atiku; Hamzah, Mohd Zaki; Saleh @ Japri, Mohd Nazre; Abdu, Arifin; Mohamed, Rosmah (Research Publication IJSER, 2017)
A participatory rural appraisal study was conducted using inclusion and exclusion criteria within twelve communities residing around Wassaniya Forest Reserve in Sokoto State Northern Nigeria, in order to ascertain the anthropological interference on the forest reserve. A multistage random sampling technique was adopted for selecting 120 respondents, from 3 villages out of 2 district each in two local government areas of Sokoto State. The results reveals different means of forest exploitation that were largely due to anthropological (human) interference. These includes collection of fuel wood, illegal hunting, sales of Non-timber forest products, over-grazing, uncontrolled bushburning, carving of local farm implements, thatching and collection of charcoal for black smith. Other means of forest exploitation found includes but not limited to collection of fruits and food from the forest, collection of herbs for medicinal purposes, Tannings, Gums and resins. The overall dependency of all the communities on forest for their daily needs shows that there is urgent needs for actions to be taken so as to diversify their income, increase their awareness on the sustainable forest management in order to reduce the risk of deforestation and desertification and the adverse effects of global warming within the area.